A Preventive Security Framework in Hadith: Exploring Mitigation and Tracing - Sidiq Hartono; Muhammad Habibi Siregar (Civiliza Publishing, 2026)
This study examines the concepts of mitigation and tracing in the Prophetic traditions (hadith) and analyzes their contribution to social security and self-defense systems. The research is motivated by the tendency of previous studies to focus primarily on hadith as a legal basis for self-defense and the use of force, while paying limited attention to their preventive and early-detection dimensions. Employing a qualitative library-based approach, this study utilizes a normative-theological perspective and thematic (mawdhu’i) hadith analysis. Primary data were drawn from relevant traditions contained in the Six Canonical Collections (Kutub al-Sittah) concerning the protection of life, property, and honor. The data were analyzed as well as contextual and intertextual analysis. The findings reveal that the hadith corpus embodies the principle of tracing as a mechanism for identifying, verifying, and detecting potential threats at an early stage, while mitigation functions as a strategy for reducing risks through the protection of life, property, and personal dignity. These findings indicate that self-defense in hadith is not merely a reactive response to an ongoing attack but constitutes an integral component of a broader preventive security framework that prioritizes risk prevention over punitive action.